Resisting Criminal Organizations: Reconceptualizing the “Political” in International Refugee Law - Khoday, Amar (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
This article examines and reconstructs the term “political” in the 1951 Convention Relating to the Status of Refugees. Individuals may be eligible for refugee status if they can prove that they have a well-founded fear of persecution for, amongst other reasons, their political opinion. At the same time, individuals are excluded from obtaining refugee status where there are serious reasons for considering that they have committed a serious non-political crime. For those resisting persons or entities wielding oppressive power, the meaning of the term “political” in these provisions has particular importance. Where the targets of resistance are criminal organizations, however, courts and tribunals have been, for the most part, reluctant to recognize such resistance as manifesting a political opinion.Given the demonstrated power of criminal organizations, this article contends that opposition to these entities should be viewed as being “political”. Through an examination of the text, context, and purpose of the Refugee Convention, it argues that a broader understanding of the term “political” is reasonable if not compelling. The article examines the conflicting jurisprudence and discourse surrounding “political opinion” and “political crimes”. Despite some strong voices in support of a more traditional state-centric interpretation, others have advanced more robust articulations that account for the dynamic nature and diversity of power transactions between citizens and powerful non-state actors. Finally, the article examines the substantial power of drug cartels and youth gangs in particular Central American states to illustrate that they exercise de facto control in substantial geographic spaces. As such, resistance to such entities should properly be viewed as “political” within the meaning of the Refugee Convention.